KEWAJIBAN SAKSI INSTRUMENTER MERAHASIAKAN ISI AKTA BERDASARKAN UNDANG-UNDANG JABATAN NOTARIS - Kusumaningrum, Ida Ayu Kade; Wairocana, I Gusti Ngurah; Made Suartha, I Dewa (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 2 (2017)DO - 10.24843/AC.2017.v02.i02.p08, 2017)
Notary as a public official who has the authority to make an authentic notarial deed, performs the duties of his/her office in accordance with the provisions of the Law of the Notary Position. In addition to the authority to make an authentic notarial deed, a notary also has an obligation of keeping the confidentiality of the contents of the notarial deed that he or she made, pursuant to the Article 16 of paragraph (1) letter f of the Amended Law of the Law of Notary Position. Notary makes authentic notarial deed based on the provisions of the Articles 1320 and 1868 of the Indonesian Civil Code, as well as the provisions contained in the Law of Notary Position. One of their obligations is presenting instrumental witnesses in the reading of the notarial deed minimum of two (2) persons. Without the presence of the 2 (two) instrumental witnesses, then the notarial deed made by or before a notary has the privately made proofing. The problems in this study were to determine whether the instrumental witnesses have the obligation keep the confidentiality of the contents of the notarial deed, as the notaries do, and to find out the liability of the instrumental witnesses for the confidentiality of their notarial deeds that they signed. This study is a normative legal research which departed from the obscurity of the applicable norm on the provisions of the Law of the Notary Position on the instrumental witnesses related to their liability to disclosure the contents of the notarial deed. This study used the related statutory approach, literature books, and dictionaries as the legal materials. The results of this study indicated that the instrumental witnesses as one of the formal requirements in the process of making an authentic notarial deed who are also the integral parts of the notary, should have an obligation to keep the confidentiality of the contents of the notarial deed. This is to prevent the leakage of secrets related to the contents of the notarial deed that may be committed by the instrumental witnesses, as well as to protect the interests of the parties on the notarial deed. A less clearly-stated provision related to the instrumental witnesses in the Law of the Notary Position has resulted in any action taken by the instrumental witnesses to become one unity with the notary, or regarded as the own responsibility of the notary. In order to provide legal certainty and legal protection to the instrumental witnesses, as well as to protect the notaries in carrying out their office, the necessary arrangements regarding the obligations and responsibilities of the instrumental witnesses should be clearly specified in the Law of the Notary Position.